Volume-Based Consolidation-to-Tumor Ratio Is a Useful Predictor for Postoperative Upstaging in Stage I and II Lung Adenocarcinomas - Shimomura, Masanori; Iwasaki, Masashi; Ishihara, Shunta; Inoue, Masayoshi (The Thoracic and Cardiovascular Surgeon, 2019)
Background We investigated the postoperative upstaging of stage I and II lung adenocarcinoma patients to identify useful predictors for accurate staging.Methods We retrospectively reviewed data from 80 consecutive patients undergoing lobectomy and mediastinal lymph node dissection for clinical stage I and II lung adenocarcinomas. We evaluated clinical variables, including the preoperative serum carcinoembryonic antigen (CEA), tumor diameter, consolidation-to-tumor ratio (CTR), maximum standardized uptake value (SUVmax) on FDG- PET, expression of epithelial growth factor receptor mutations, and pathological invasion to the pleura (pl), lymph duct (ly), and vein (v).Results Eleven patients (13.8%) showed postoperative upstaging. Three cases had pN1 migrating from cN0, four cases had pN2 from cN0, and four cases showed malignant pleural effusion. The CEA level and CTR were significantly higher in the upstaging group. The tumors in the upstaging group showed more frequent pathological invasion to the visceral pleura and vein. In patients with 3 cm or smaller consolidation, two-dimensional (2D)-CTR and volume-based CTR were independent predictors of upstaging.Conclusions Volume-based CTR could be a useful predictor for accurate clinical staging in stage I and II adenocarcinoma patients in addition to consolidation size, serum CEA level, and 2D-CTR. Both volume-based and 2D-CTRs might be especially useful in T1 diseases.
Keywords: lung cancer; consolidation-to-tumor ratio; clinical stage